2021
DOI: 10.1371/journal.pone.0258305
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an increased number of physical education lessons on the motor performance of adolescents–A non-interventional cohort study

Abstract: Increasing the amount of regular physical education lessons in school is currently discussed in many countries in order to increase physical activity in youth. The purpose of this study was to compare the motor performance of pupils from an observation group participating in a school trial of two additional physical education lessons (5 lessons of each 50 min/week) without a specific intervention program to a control group with a regular amount of three physical education lessons (3 lessons of each 50 min/week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Our study revealed the gender difference, in which the Slovak adolescent boys were significantly more physically active than adolescent girls (p < 0.01), and that's in accordance with many previous studies (Mayo et al, 2020;Cowley et al, 2021;Pate et al, 2022;Ricardo et al, 2022). For more complete insight into the pattern of physical activity, it is required to separately analyze each physical activity domain.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study revealed the gender difference, in which the Slovak adolescent boys were significantly more physically active than adolescent girls (p < 0.01), and that's in accordance with many previous studies (Mayo et al, 2020;Cowley et al, 2021;Pate et al, 2022;Ricardo et al, 2022). For more complete insight into the pattern of physical activity, it is required to separately analyze each physical activity domain.…”
Section: Discussionsupporting
confidence: 91%
“…Despite of having administered one of the longest school closures globally, schooling in Slovakia was not adequately prepared for long-term teaching through remote access, which brought fundamental problems, including physical education. School physical education provides a context for regular and structured physical activity participation (Uddin et al, 2020) and represents the only opportunity of engaging in physical activity (Bali, 2016;Reif et al, 2021). According to results of present study, during the second wave of Covid-19 pandemic, on average, 60.55 % (n = 1438) of Slovak adolescents (n = 2375) engaged in high physical activity, with increasingly larger number of Slovak adolescents boys (65.25 %, n = 704), compared to adolescent girls (55.86 %, n = 723), which we consider as a positive finding, however the IPAQ-SF overestimate physical activity levels to a greater extent (from 36 % to 173 %), compared to existing physical activity questionnaires (Lee et al, 2011;, and therefore the absolute physical activity levels must be interpreted with a caution (Grimm et al, 2012;Wanner et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, membership in a sports club has positive effects through its social structure, the shared norms and values, and the commitment to fairness and respect [16,17]. In the long run, membership in a sports club and active participation in sports activities positively affect physical, mental and social well-being and thus contribute to an overall increase in the quality of life [18][19][20][21][22]. This holds true both for ball sports as well as other sports [23].…”
Section: Introductionmentioning
confidence: 99%
“…Motor performance skill (MPS) was considered as an important issue and got attention by several major countries in the world [26]. In this study, the global term MPS was used to describe fundamental movement skills including when displaying skills in sports situations [27], such as jumping, running, throwing, hitting [28,29]. However, another definition explains that MPS is an advanced level of fundamental movement skills that can be used in dynamic situations to apply and test their skills in a sporting activity [30].…”
Section: Introductionmentioning
confidence: 99%